PENGEMBANGAN MEDIA PEMBELAJARAN ANIMATION SHORT MOVIE BERBASIS CANVA UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM PENCERNAAN DI KELAS XI SMA SWASTA YP HKBP PEMATANGSIANTAR - Esra Fransiska Pelawi; Winarto Silaban; Gloria Sirait (Smart Education, 2025)
Abstract: This study aims to (1) Determine the feasibility test of Canva-based animation short movie media on digestive system material. (2) Determine students' responses to the use of Canva-based animation short movie media on digestive system material. (3) Determine the effect of Canva-based animation short movie media on student learning outcomes on digestive system material in class XI of YP HKBP Pematangsiantar Private High School. This study uses the Research and Development (R&D) method using the ADDIE development model. The research subjects used were class XI of YP HKBP Pematangsiantar Private High School, with class XI-3 as the experimental class and class XI-4 as the control class. Data collection instruments include validation by material experts, media experts, subject teachers, as well as learning outcome tests and student response questionnaires. Data analysis was conducted through media feasibility trials, product trials, and learning outcome analysis. The validation results showed an average feasibility percentage of 95% (very feasible category), with details of content/material feasibility 93%, presentation 94%, design 94% and language 98%. Student learning outcomes increased from an average value of 63.3% before using the media to 80.0% after using the media, indicating that there was a positive influence on learning outcomes. Student responses to the media were in the